Karakterisasi Plasma Nutfah Kangkung - Yenni Kusandriyani; nFN Luthfy (Buletin Plasma Nutfah, 2006)
Characterization of Ipomoea reptans germplasm collection were done in order to describe the accessions and to utilize as working collection materials for breeding program. Description was aimed to identify the new collections of 15 accessions I. reptans which were taken from IVEGRI (Indonesia Vegetable Goverment Research Institute) germplasm collection. The experiment was carried out in Subang station (100 m asl) in dry season 2002. Each accession were planted 40 plant per plot of I. reptans with plant distance 20 x 30 cm. The plants of were fertilized with stable manure 20 t/ha and NPK (15 : 15 : 15) 500 kg/ha. The result of the study was a description of genetic resources that will be exchanged and utilized in breeding for high yielding varieties of I. reptans with better quality. AbstrakKarakterisasi plasma nutfah kangkung dilakukan untuk mendapatkan deskripsi sifat tanaman dan sebagai bahan working collection yang akan digunakan sebagai bahan dalam program pemuliaan. Penelitian mencakup 15 nomor aksesi kangkung di Kebun Percobaan Subang (100 m dpl) Jawa Barat pada musim kemarau 2002, tiap nomor dari masing-masing aksesi ditanam sebanyak 40 tanaman. Tanaman diberi pupuk kandang domba dengan takaran 20 t/ha dan NPK (15 : 15 : 15) 500 kg/ha. Hasil penelitian ini menghasilkan deskripsi plasma nutfah tanaman kangkung untuk pertukaran informasi mengenai sumber genetik yang akan digunakan dalam pemuliaan untuk mendapatkan varietas unggul dengan kualitas yang lebih baik.